تصمیم حاسوبي لعدسة كھروستاتیكیة ثلاثیة الأقطاب - أ.د.سمیر خضر العاني ندى عبد الفتاح محمد (College of Education for Women, 2019)
A low aberration electrostatic lens of three electrode was design, The electrode shapes were determined using solution of Laplace equation . A new Computational technique were used to design an electrostatic lens which depends on the determination polynomial function of the third order with the solution of axial - equation to find the trajectory of particles which satisfy the suggested potential function besides the other optical properties such as brightness ,perveance and current density. The results showed low values of spherical and chromatic aberrations comparing with other searches about1.4 for spherical aberration and 0.98 of chromatic aberration with values of potential of 20 which are considered as good criteria for good lens's design.